EFL GRADUATE STUDENTS’ INNER SPEECH AND IMPLEMENTATIONS OF THEIR ACADEMIC WRITING DEVELOPMENT - Lailatun Nurul Aniq; NURKAMTO, JOKO; SISWANDARI, SISWANDARI; DRAJATI, NUR ARIFAH (SEAQIL Journal of Language Education, 2025)
All around the world, colleges and universities have serious concerns about academic writing. All university and college students, especially those studying English as a second language (EFL), need to generate various textual forms for their academic education. Higher education students who do not communicate English as their native language encounter many linguistic, discursive, and cognitive difficulties when there is an educational requirement to publish academic writing in a reputable international journal. They suffer enormous barriers concerning their viewpoints as well. The purpose of this study is to investigate the particular writing experiences employed by graduate students in the English education program and assess how these practices influence their thesis and other scholarly publications. This research followed Barkhuizen et al.’s (2013) narrative inquiry paradigm. Through WhatsApp, the students engaged in several lengthy semi-structured interviews that were continued by such focus group discussions. We scrutinized and looked at their scholarly articles and theses in these dialogic interactions for two months, among other forms of English scholarly work. This research revealed that participants encountered conflict and tensions in their writing practices, particularly within specialties that require critical and suitable attention. Conjectured narratives of personal encounters in this research would be utilized as a guidance document to help evaluate students' English academic writing habits to meet their intended results. This has ramifications for how English research and educational writing is understood.